2014
DOI: 10.1088/0067-0049/213/2/29
|View full text |Cite
|
Sign up to set email alerts
|

Warm Breeze From the Starboard Bow: A New Population of Neutral Helium in the Heliosphere

Abstract: We investigate the signals from neutral helium atoms observed in situ from Earth orbit in 2010 by the Interstellar Boundary Explorer (IBEX). The full helium signal observed during the 2010 observation season can be explained as a superposition of pristine neutral interstellar He gas and an additional population of neutral helium that we call the Warm Breeze. The Warm Breeze is approximately two-fold slower and 2.5 times warmer than the primary interstellar He population, and its density in front of the heliosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 59 publications
6
119
1
Order By: Relevance
“…( ) y Thus, averaging over spin-angle bins does not introduce any significant additional error. In all, the calculation load in this aspect is reduced by ∼30% in comparison with the model (2) approach used by Bzowski et al (2012) and Kubiak et al (2014) and, additionally, the accuracy is higher. We have verified that using lower-order polynomials does not always provide a sufficient accuracy, while using a higher order method would not necessarily bring better results, but certainly would increase the calculation load in comparison with method (2).…”
Section: Integration Of the Flux Over The Spin-angle Binsmentioning
confidence: 92%
See 2 more Smart Citations
“…( ) y Thus, averaging over spin-angle bins does not introduce any significant additional error. In all, the calculation load in this aspect is reduced by ∼30% in comparison with the model (2) approach used by Bzowski et al (2012) and Kubiak et al (2014) and, additionally, the accuracy is higher. We have verified that using lower-order polynomials does not always provide a sufficient accuracy, while using a higher order method would not necessarily bring better results, but certainly would increase the calculation load in comparison with method (2).…”
Section: Integration Of the Flux Over The Spin-angle Binsmentioning
confidence: 92%
“…It was also used by Bzowski et al (2014) to re-analyze observations from GAS/Ulysses, including the first analysis of the data from the last Ulysses orbit in 2007, which had previously not been analyzed. This analysis brought a flow vector similar to the original analysis by Witte (2004), but a temperature higher by at least ∼1000 K. It was also used by Bzowski et al (2013a) and Park et al (2014) to analyze the abundance of Ne/O ratio in the LIC based on IBEX-Lo measurements, and by Kubiak et al (2014) to discover the additional ISN He population detected by IBEX-Lo dubbed the Warm Breeze, which is very likely the secondary heliospheric population of ISN He. The WTPM model was also used by Kubiak et al (2013) to predict possibilities of detection of the ISN D flux by IBEX-Lo, subsequently found in the IBEX-Lo signal by Rodríguez Moreno et al (2013Moreno et al ( , 2014.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Third, the green pixels between λ=160°and 200°r epresent the secondary ISN He population, which is also called "Warm Breeze" Kubiak et al 2014Kubiak et al , 2016. Because the logarithmic representation does not show the directional distribution of this population in detail, we compare the latitude profiles of the count rates along the latitudinal swaths between λ=160°and 300°in the He maps.…”
Section: He Maps With the Sputtering Correctionsmentioning
confidence: 99%
“…Bzowski et al (2012) hypothesizedthe secondary population of the ISN He atoms to describe the differences between simulations and observations. Kubiak et al (2014) discovered what they termed the "Warm Breeze," which is slower and warmer than the primary ISN He population, and its flow direction differs by about 19°from the ISN gas flow. Kubiak et al (2016) revisited the inflow direction of the Warm Breeze and found that it is almost co-planar with the inflow directions of ISN H and He and the direction to the center of IBEX Ribbon.…”
Section: Introductionmentioning
confidence: 99%